LC-MS/MS methodology development and validation for the screening and quantification of five antibiotics in water. Issue 9 (17th February 2022) - Nunes, M. João; Paz, Victória; Cordas, Cristina M.; Noronha, João Paulo; Branco, Luís C.
Abstract : A screening LC-MS/MS method was established for five antibiotics. The optimization and validation proved that it is suitable for the identification and quantification. The utility for the removal process of antibiotics from water was proven. Abstract : The generalized use of antibiotics in veterinary medicine may cause the development of antibiotic resistance, namely, in farmed fish, and subsequently, transmission of such resistance to humans. To overcome this serious problem, it is necessary to improve the efficiency of antibiotic removal processes from water, and a route for attaining that goal is the use of hydrophobic ionic liquids. LC-MS/MS is an analytical technique with proven utility for pharmaceutical identification and quantification. A methodology for the identification and quantification of five antibiotics, namely ampicillin, amoxicillin, chloramphenicol, enrofloxacin and oxytetracycline, from four families, namely β-lactams, phenicols, quinolones and tetracyclines, was developed and validated using one SPE extraction and clean-up step for detection analysis by LC-MS/MS. The selected linear range for each analyte is as follows: 5–200 ng mL −1 for ampicillin; 0.1–200 ng mL −1 for amoxicillin and chloramphenicol; and 1–200 ng mL −1 for enrofloxacin and oxytetracycline, respectively. The limits of detection for each target analyte vary between 0.01 ng mL −1 and 0.81 ng mL −1, and the limits of quantification for each target analyte vary between 0.1 ng mL −1 and 5 ng mL −1 for the five antibiotics under study. The extraction recovery value range is between 89.91% and 100.33%. The validation proved that the developed methodology is suitable for the identification and quantification of ampicillin, amoxicillin, chloramphenicol, enrofloxacin and oxytetracycline. After validation, this new assay was successfully applied to a liquid–liquid extraction process using a hydrophobic ionic liquid.